COMPARISON OF SYSTEMS OF CARS FOR EXTREME CONDITIONS LOGGING - Shirnin, Alexander Yurievich; Shirnin, Yuri Aleksandrovich (Journal of Applied Engineering Science, 2016)
Technological schemes for development of cutting areas in extreme conditions which basis the combined way of skidding is are submitted. Systems of cars for development of cutting areas in such conditions are offered this way. Comparison of the technological processes which are carried out by these systems of cars by the following criteria is carried out: level of mechanization of work, expense of time for preparation of 1 m3, coefficient of environmental friendliness of the technological scheme, power consumption.
Keywords: The evaluation criteria of technological processes; Combined hauling wood